Kiskisitotaso, Don’t Forget Yourself: Indigenous Resurgence in David A. Robertson’s Barren Grounds - Anah-Jayne Samuelson (Canada and Beyond)
David A. Robertson’s (Norway House Cree) children’s novel The Barren Grounds (2020) intervenes in Canada’s historical and ongoing child welfare systems’ impacts on Indigenous children and youth. This article argues that Indigenous children’s literature could significantly contribute to the ongoing efforts towards reconciliation in Canada. Robertson, as a specific example of this, presents a decolonized version of foster care that is rooted in Indigenous resurgence and grounded normativity. This representation encourages young readers to reconsider entrenched settler-colonial structures that, potentially, advance the projects of reconciliation and decolonization in Canada. Barren Grounds considers alternatives to current foster care structures that are predicated on Indigenous foster children and youth being directly reconnected with Indigenous peoples, lands, and knowledge systems. This reconnection transmits grounded normative ethics and builds Indigenous resurgence—both of which Robertson demonstrates are key in combating settler-induced disconnection and dispossession.